Characterization and Analysis of Hardness, Microstructure, and Crystallography of SS 304-Sheathed MgB2 Superconducting Wires - Rivai, Rizky Ramadhani; Pramono, Andika Widya; Priyanto, Tri Hardi; Maghfirah, Awan (National Research and Innovation Agency (BRIN), 2023)
This research was conducted to analyze the hardness, microstructural morphology, and crystallography of the MgB2 compound in the form of a SS 304-sheathed superconducting wire. MgB2 superconducting wire with SS 304 outer sheath was manufactured using an ex-situ rolling process. The results of the Vickers hardness test with a load of 0.3 N showed the MgB2 hardness value of 355.1 HV. The results of observations with SEM-EDS (scanning electron microscopy-energy dispersive spectroscopy) showed the agglomerations of the second phase of (Mg)B-O with various compositions due to the rolling process. There was also a longitudinal crack in the MgB2 area due to the work-hardening phenomenon in the brittle MgB2 solid. There were no obvious Bragg peaks in the MgB2 phase. The detected Bragg peaks came from the austenitic (g-Fe) of SS 304-sheath.